Pause, Traveler - Hollowell, Erin Coughlin, 1965- (Book collections on Project MUSE., 2013)
Pause, Traveler is a journey through the dark heart of the American landscape, from New York City to Alaska. These poems search for redemption in the most unlikely places: Circus World Museum, an Iceworm Festival, a frozen gas station in Alaska. Traversing the difficult terrain of damaged relationships and misplaced affection, this collection finds hope in the fractured beauty of the world.